The communicative role of the Catholic Church in Poland in the 2015 presidential election and its perception by the public. Issue 1 (1st January 2016) - Lesniczak, Rafal
Abstract: The aim of this paper is to determine the role of the Catholic Church hierarchy in the 2015 presidential election in Poland. The author will analyse the content of the most important institutional messages of the Polish Episcopal Conference in which bishops express their opinions on presidential election and particular candidates. This case study also includes the analysis of the content of the most important Polish Catholic weekly magazines ( Gość Niedzielny, Niedziela ) and the analysis of the method of presenting the role of the Catholic Church as a potential political player in the most important all-Poland daily papers ( Gazeta Wyborcza, Rzeczpospolita ) and opinion weekly magazines ( Newsweek Polska, Polityka ).